PENGARUH BEAUTY INFLUENCER, BRAND IMAGE, DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINTIFIC DI KALANGAN GEN Z DI KOTA MANADO - Montolalu, Nehemia Emilly (Universitas Sam Ratulangi, 2026)
Generation Z is a consumer group highly adaptable to technology and social media, making beauty influencers and information from their social circle highly influential in their purchasing decisions. Skintific, as a growing brand in the cosmetics and skincare market, needs to understand these factors to maintain and increase its market turnover. This research uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to a sample of Generation Z in Manado City who have purchased Skintific products. The sampling technique used was purposive sampling. The collected data was then analyzed using multiple regression analysis to test the research hypotheses. The results of this study are expected to provide evidence regarding the extent to which beauty influencers, brand image, and word-of-mouth contribute to purchasing decisions for Skintific products among Gen Z. Furthermore, the findings should positively impact Skintific in designing more effective marketing strategies, especially in leveraging beauty influencers, building a strong brand image, and encouraging the spread of positive word-of-mouth among target consumers. Key word: Beauty Influencer, Brand Image, Word of Mouth, Purchase Decision, Generation Z, Skintific.